Sikiöaikana päihteille altistuneet lapset aikuisuuden kynnyksellä – Yhteenveto ADEF Helsinki -tutkimusprojektin tuloksista - Koponen, Anne; Nissinen, Niina-Maria; Gissler, Mika; Autti-Rämö, Ilona; Kahila, Hanna; Sarkola, Taisto (Sosiaalilääketieteellinen Aikakauslehti, 2024)
Children with prenatal substance exposure on the threshold of adulthood – A summary of the results from the Anonyme-study A comprehensive picture of developmental outcomes and associated environmental risks among youth with prenatal substance exposure (PSE) is scarce in Finland and other countries as well. This longitudinal register-based cohort study compared youth with PSE (n=615) and matched unexposed controls (n=1787) regarding mental health, completed secondary education, financial social support, and injuries and poisoning. The follow-up lasted from birth until the end of 2016. Hospital medical records (exposure) and register data (outcomes) were merged and analysed mainly by logistic and Cox regression analysis, and mediation analysis. A majority (63.4%) of exposed youth had been in out-of-home care (OHC, controls 8.2%) and the prevalence of mental and behavioural disorders was two times higher (54.6% vs. 26.4%). In addition, hospital care for injuries and poisoning, delay in secondary education completion, and financial difficulties were more common. Those with OHC, poor health at birth and many maternal risks had the poorest outcomes. Cumulative risk factors were associated with all developmental outcomes in both groups and decreased the differences between them. The environment was strongly associated with developmental outcomes among youth with PSE. Child and adolescent health is best promoted by identifying risk pregnancies and supporting families during the prenatal and early childhood periods. Key words: Prenatal substance exposure; youth; adverse childhood experiences; developmental outcomes